Electrifying Africa: how to make Europe's contribution count - Simone Tagliapietra (Bruegel, 2017)
Electrification is one of sub-Saharan Africa's most pressing socio-economic challenges. Less than a third of the sub-Saharan population has access to electricity, and around 600,000 premature deaths are caused each year by household air pollution resulting from the use of polluting fuels for cooking and lighting. Solving this issue is a fundamental prerequisite for unleashing sub-Saharan Africa's economic potential. Given the magnitude of the challenge, only a joint effort involving sub-Saharan African countries and international public and private parties would pave the way to a solution. Sub-Saharan African countries should be the first to move. They should reform the governance of their energy sectors, in particular by reforming their generally inefficient state-owned electricity utilities, and by phasing-out market-distorting energy subsidies. Without such reforms, international investment will never scale-up across sub-Saharan Africa. International public and private parties must play a key role in facilitating sub-Saharan Africa's energy transformation, particularly the electrification of rural areas, where three-fifths of the sub-Saharan African population lives. International public support is particularly important to crowd-in international private investors, most notably through innovative public-private partnerships. China and the United States are already engaged in electrification in sub-Saharan Africa. China has substantially invested in large-scale electricity projects, while the US has put in place a comprehensive initiative - Power Africa - to scale-up electrification, particularly in rural areas, through public-private partnerships. Europe has, instead, created a myriad of fragmented initiatives to promote electrification in sub-Saharan Africa, limiting their potential leverage in crowding-in private investment and in stimulating energy sector reforms in sub-Saharan African countries. This sub-optimal situation should be changed by coordinating the initiatives of European institutions and EU countries through a unique platform. We propose such a platform: the EU Electrify Africa Hotspot.
Keywords: 330